К вопросу оценки показателей, характеризующих структуру горных пород, для совершенствования процессов производства щебня - Shchukin P. O., Kameneva E. E., Voronin I. A. (Innovative technologies in science and education, 2017)
It shows the need for a particular type of rock to identify characteristics that predict size distribution of the crushed product, depending on its strength characteristics, size and disintegration parameters.
Keywords: интеллектуальная собственность; исследования; горные породы; дезинтеграция; research; rocks; disintegration